Dynamics of Cultural Transfer in Pluricultural Learning of Bahasa Indonesia untuk Penutur Asing - Asteria, Prima Vidya; Pramesty, Meydiana Dyah; Yossilia, Putri Bunga; Suyoto, Suyoto; Maiklad, Chamaipak (Journal of Innovation in Educational and Cultural Research, 2026)
As students of BIPA (Bahasa Indonesia untuk Penutur Asing or Indonesian for Foreign Speakers) learning, cultural aspects are fundamental to understand. One reason is that having cultural awareness can increase the success of the language learning process, including BIPA learning. This study aims to describe the dynamics of cultural transfer and its challenges in Indonesian language learning for pluricultural-based foreign speakers. This research applies a qualitative method with a descriptive approach. The results indicate that cultural learning for BIPA students is achieved through three key aspects: cultural products, cultural values, and cultural behavior. Inherent teaching methods are more recommended than separate teaching methods. The challenges of cultural transfer in BIPA learning start with: 1) very different cultural backgrounds; 2) BIPA programs tend to be theoretical; 3) Indonesian culture is very diverse and complex; 4) cultural education requires teachers to have the capacity and experience in cultural understanding and communication; and 5) the fast speech tempo of Indonesian society. This article provides a comprehensive overview of the dynamic process of cultural transfer and the challenges of learning Indonesian for pluricultural-based foreign speakers. This research is expected to contribute to the development of BIPA teaching-learning activities that are more adaptive, contextual, and capable of enhancing cultural understanding for learners.